Diagnostic value and safety of contact laser-assisted endobronchial ultrasound-guided tunnel drilling biopsy in mediastinal and hilar lymphadenopathy: a retrospective study - Wenyu Zhan; Tian Wang; Changqing Yang; Yubao Wang; Nansheng Wan; Jing Feng (Frontiers in Medicine)
IntroductionMediastinal and hilar lymphadenopathies are primarily diagnosed pathologically. Contact laser-assisted endobronchial ultrasound-guided tunnel drilling biopsy (EBUS-TDB), which uses a laser as a tunneling and incision tool, may yield more satisfactory specimens than conventional endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), thereby improving the diagnostic yield. This study aims to evaluate the diagnostic value and safety of contact laser-assisted EBUS-TDB compared to EBUS-TBNA in the assessment of mediastinal and hilar lymph nodes.MethodsThis retrospective study included patients who presented to our hospital between October 2022 and April 2024 with mediastinal or hilar lymph nodes of short diameter ≥ 1 cm on computed tomography (CT) or abnormally increased lymph node metabolism on positron emission tomography (PET)-CT. All patients underwent both EBUS-TBNA and EBUS-TDB procedures successively.ResultsOverall, 278 patients were included in the study, and 244 cases were confirmed. The diagnostic rates (p-values) for EBUS-TDB and EBUS-TBNA in pulmonary and extrapulmonary malignancies, lymphoma, sarcoidosis, and lymph node tuberculosis were 96.6% vs. 76.3% (0.043), 100% vs. 67.7% (−), 88.9% vs. 31.1% (0.555), and 69.2% vs. 30.8% (0.049), respectively. No serious adverse events occurred during or after either procedure.ConclusionContact laser-assisted EBUS-TBNB demonstrates superior diagnostic performance compared to EBUS-TBNA for the evaluation of mediastinal or hilar lymph nodes, making it an alternative to EBUS-TBNA for enhanced diagnostic precision.